Inequalities on Generalized Sasakian Space Forms - Rehman, Najma Abdul; Ghaffar, Abdul; Abedi, Esmaeil; İnç, Mustafa; Kaabar, Mohammed K. A. (Wiley, 2021)
In this paper, we find the second variational formula for a generalized Sasakian space form admitting a semisymmetric metric connection. Inequalities regarding the stability criteria of a compact generalized Sasakian space form admitting a semisymmetric metric connection are established.
Keywords: Harmonic Maps; Stability